(untitled) (Tanzania Medical Journal, 2023)
Background A woman feels secure when she is continuously cared for and supported during childbirth. Birth companion is one of the key recommendations for positive childbirth experiences as it promotes women’s sense of self-control in the labour process. The benefits of a birth companion are well known but not routinely practiced in Tanzania. Broad Objective This paper describes the experiences of mothers who had a companion during labour and delivery. Methodology An explorative qualitative study was carried out among 12 purposively recruited postnatal mothers at a health centre in Kigoma region. Data were collected using in-depth interviews and analysed by an inductive thematic approach. Findings Women commonly chose their family members to be their birth companions who provided them with continuous emotional, physical and practical support and facilitated communication among women, providers and relatives during labour and delivery. Conclusion and recommendations The support and care from the birth companions, gave women strength and confidence to cope with the stress of labour throughout the birthing process. Women received continuous care and support from birth companions of their choice who also played a key communication role that facilitated prompt care. Mechanisms are required to ensure birth companionship is integrated into the health system to support women during childbirth.